The labor market of the Republic of Kazakhstan in the context of global challenges - Berdibekov, A.B.; Kaigorodtsev, A.A.; Bordiyanu, I.V.; Brauweiler, H.C. (BUKETOV BUSINESS REVIEW, 2020)
Object: The object of the research is analysis of the current state of the labor market of the Republic of Kazakhstan and determination of promising directions of its development. Methods: Systematic approach, abstract-logical and monographic analysis, horizontal and vertical analysis of official statistical information and the state of the labor market. Findings: The characteristic of global challenges to the effective functioning of the Kazakhstan labor market is given. A quantitative assessment of indicators characterizing the dynamics of the labor market of the republic was carried out. The structure of employed and unemployed people is given. As a result of comparing the number of vacancies and resumes presented on the electronic labor exchange, it is concluded that there is a shortage of personnel in the republic. The most and least demanded professions are determined. The characteristic of the level of differentiation in wages of workers is given. The analysis of the system of state regulation of the labor market. The methods of regulation aimed at solving the problems of the domestic labor market, both on a planned basis and in emergency situations, are considered. The characteristic of the current results of the implementation of the Program for the Development of Productive Employment and Mass Entrepreneurship for 2017-2021 "Enbek" is given. The main directions of development of the Kazakhstan labor market are determined. Conclusions: Effective employment should be ensured by increasing competitiveness, professional mobility and efficient use of labor; it is necessary to ensure the priority creation of jobs in high-tech import-substituting and exportoriented industries, training, retraining and advanced training of personnel taking into account the future needs of the economy, improving mechanisms to promote self-employment of the population.